Identifying Characteristics of Frailty in Female Mice Using a Phenotype Assessment Tool. (8th April 2019) - Kwak, Dongmin; Baumann, Cory W; Thompson, LaDora V
Abstract: Preclinical studies are important in identifying the underlying mechanisms contributing to frailty. Frailty studies have mainly focused on male rodents with little directed at female rodents. Therefore, the purposes of this study were to identify the onset and prevalence of frailty across the life span in female mice, and to determine if frailty predicts mortality. Female C57BL/6 ( n = 27) mice starting at 17 months of age were assessed across the life span using a frailty phenotype, which included body weight, walking speed, strength, endurance, and physical activity. The onset of frailty occurred at approximately 17 months (1/27 mice), with the prevalence of frailty increasing thereafter. At 17 months, 11.1% of the mice were pre-frail and by 26 months peaked at 36.9%. The percentage of frail mice progressively increased up to 66.7% at 32 months. Non-frail mice lived to 29 months whereas frail/pre-frail mice lived only to 26 months ( p = .04). In closing, using a mouse frailty phenotype, we are able to identify that the prevalence of frailty in female mice increases across the life span and accurately predicts mortality. Together, this frailty phenotype has the potential to yield information about the underlying mechanisms contributing to frailty.